Health and Growth of Black Pine outside Its Natural Distribution Range in the Romanian Carpathians - Tudoran, Gheorghe Marian; Cicsa, Avram; Dobre, Alexandru-Claudiu; Cicsa, Maria; Pascu, Ionut-Silviu; Leca, Stefan (Forests, MDPI, MDPI AG, Grosspeteranlage 5, CH-4052 BASEL, SWITZERLAND, 2023)
In the last decade, coniferous stands outside their natural range in Romania have experienced declines in both their health and growth and, in tandem with global climate trends, these forests are becoming even more threatened. We studied the relationship between tree growth and defoliation as an indicator of tree health. The data came from black pine stands monitored from 2012 to 2021 in the Postavarul Massif in the Romanian Carpathians. Analyses were carried out on 508 individual trees based on their defoliation and radial growth data and also at the stand level. The results revealed an increase in the percentage of tree defoliation from 17% to 38% during the studied decade, along with 13.5% tree mortality. Over the decade, radial growth showed a negative trend, driven significantly by defoliation. The biometric parameters of the trees did not influence their percentage of defoliation. In contrast, spring/summer droughts associated with high temperatures affect the health and growth of trees. Models generated from the temperature-defoliation-radial-growth relationship estimated a significant continuous reduction in the radial growth of the trees of 0.5%-0.6% for each 1% increase in defoliation. Under the site conditions of the investigated stands, an increase in basal area and stocking degree significantly increased stand defoliation. This was further accentuated when the pine stand included an understory of young trees. As a rule, in the interest of production, stands are kept dense to fully exploit the site, but thinning may become necessary to protect these stands and ensure their survival as the climate changes.